The strategic land development of FELDA and the effect on the status socio economic rural society case study: Felda Tenang Labis Segamat Johor Department of estate management / Nor Niza Mahmud - Mahmud, Nor Niza (2010)
Land development is an important strategy in the development of agriculture sector in Malaysia and developing countries. The main objective of this strategy is to eradicate poverty in the agricultural sector through increased earnings and providing employment opportunities to farmers who have land, idle land and rehabilitation. For this purpose, the government has established several agencies to develop and improve the soil while improving the standard of the rural economy. One of the agencies established the Federal Land Development Authority (FELDA). The convergence of these studies focused on the effectiveness of land development schemes have been implemented by FELDA in Felda Tenang, Labis Segamat Johor. The objective of this study is to "identify land development strategy that was implemented by FELDA in the development of idle land through land consolidation and rehabilitation and the effect of socio-economic level of rural residents, especially participants of the program. Method of data collection for this study involves the collection of two main data collection of secondary data and primary data. The results of this analysis also found that rural poverty has been reduced; the quality of life has increased with the increases of property. Once the findings is made, the proposal was made to improve the land development by FELDA as preparing more specific guidelines, improve the labor problem and encouraging entrepreneurship program, the transformation of the labor force. Therefore, the FELDA land development plan will benefit and be able to improve the socio-economic status, particularly with the establishment of rural population various schemes of land development program.